Inovasi dan Kreativitas Sebagai Kunci Keberhasilan Wirausaha di Era Ekonomi Digital - Dwi Syaputra; Ahmad Afandi (Lembaga Pengembangan Kinerja Dosen, 2025)
Community Service (KKN) is one method to implement the Tri Dharma of Higher Education through community service activities. The Independent KKN Project from the University of Muhammadiyah North Sumatra in 2025 was implemented in Dolok Kahean Village, Tapian Dolok District, Simalungun Regency, with the theme